A Analisis Persepsi Konsumen Terhadap Keputusan Pembelian Pada Perumahan Grand Residence Makale Kabupaten Tana Toraja - Tapparan, Samuel Randy; Justian, Justian; Nursita, Lisa (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2021)
Abstract This study aims to determine how consumers' perceptions of purchasing decisions at Grand Residence Makale Housing, Tana Toraja Regency. This type of research is descriptive quantitative research and data collection techniques carried out in this research are field research and library research. The data collection procedure was carried out by means of observation, interviews, and documentation. The types of data used are primary data and secondary data. The percentage of the highest average perception per indicator is 68.4% of all indicators that the Makale Grand Residence housing does have a good or positive perception Keywords: Perception, Consumer, Purchase decision.